AKSARA WREASTRA DAN WIJAKSARA DALAM AKSARA BALI (STUDI STRUKTUR DAN MAKNA DALAM AGAMA HINDU) - Widiantana, I Kadek; Wiradnyana, I Made (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2020)
Humans as socio-cultural creatures can never be separated from the use of symbols, including symbols related to linguistics, which are used as sacred symbols in Hinduism in Bali, namely scripts, both Wreastra and Wijaksara Scripts. Hindus in Bali, for the most part, consider that the Wreastra script is only an ordinary script, which has no philosophical meaning, making researchers interested in studying the philosophical meaning in the Wreastra Script that is accompanied by the study of Wijaksara Script.Starting from this background, there are several research problem formulations, namely what is the meaning of the Wreastra and the Wijaksara Scripts in Hinduism. To answer these problems, the researcher use structural theories, semiotic theories, and theories of meaning. This type of research is qualitative research, with a philosophical-symbolic approach.The results of this study are the Wreastra and Wijaksara scripts have a meaning as worship to the God with all its manifestations adjusted to the script used. The application of the Wreastra and Wijaksara scripts in religious ritual activities in Bali as part of socio-religious activities can be seen from its use in the Rerajahang Kajang, Ulap-Ulap and Pecaruan rites.The conclusion that can be drawn is that the Wreastra and Wijaksara scripts have a high philosophical meaning of God, so that in writing and its use is not arbitrary, always starting with prayer of worship to the God.